Parental involvement and kindergarten children literacy competencies: socio-pedagogical and developmental implications - Penderi, Efthymia; Papanastasatou, Irini (Psychology: the Journal of the Hellenic Psychological Society, 2022)
Current theories on the literacy acquisition recognize the role of social experiences and the importance of interactions between children and parents during this process. This paper investigates the link between the involvement of parents of preschool children in relation to literacy and children’s literacy competencies based on parent reports. 214 parents from various regions nationwide participated in the survey. For the purposes of data collection, the Parental Involvement Questionnaire for Kindergarten Literacy and the Kindergarten Children’s Literacy Competencies Scale, parent version were administered. Findings confirmed the link between perceived parental involvement practices and preschool children’s literacy competencies. The predictive power of factors related to the qualitative dimension of parental involvement in children’s literacy and parent-child interaction in literacy-related activities at home was demonstrated. The role of the parent’s gender and the availability of books for children at home for the development of relevant skills was found to be important. The contribution of children’s age in predicting literacy competences, with parents reporting higher levels for younger children, has implications for the sociopedagogical mission of the school to support family role by promoting parents’ knowledge and quality involvement for positive children’s outcomes.